2003
DOI: 10.1046/j.1365-2958.2003.03751.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two Pseudomonas putida lipopeptide biosurfactants, putisolvin I and II, which inhibit biofilm formation and break down existing biofilms

Abstract: SummaryPseudomonas putida strain PCL1445 was isolated from roots of plants, grown on a site polluted with polycyclic aromatic hydrocarbons. PCL1445 produces biosurfactant activity at the end of the exponential growth phase. High-performance liquid chromatography (HPLC) analysis of supernatant extracts of PCL1445 showed two peaks with surfacetension reducing activity, tentatively assigned as biosurfactants putisolvin I and putisolvin II and was followed by structural analyses. A transposon mutant of PCL1445, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
243
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(265 citation statements)
references
References 45 publications
13
243
1
8
Order By: Relevance
“…Allesen-Holm et al (2006) found that for the lasI/rhlI mutant with thin and flat biofilms, the extracellular DNAs was very little. The nuclease gene nuc contributed to biofilm detachment of Staphylococcus aureus (Kuier et al 2004), and was able to degrade the extracellular nucleic acids. The quantitative results of the mRNA expression level on nuc increased to 17.03 fold of the control with 0.04 mg ml -1 DKP (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Allesen-Holm et al (2006) found that for the lasI/rhlI mutant with thin and flat biofilms, the extracellular DNAs was very little. The nuclease gene nuc contributed to biofilm detachment of Staphylococcus aureus (Kuier et al 2004), and was able to degrade the extracellular nucleic acids. The quantitative results of the mRNA expression level on nuc increased to 17.03 fold of the control with 0.04 mg ml -1 DKP (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used techniques are organic solvent extractions with chloroform and methanol, petroleum ether, ethyl acetate, n-hexane and ether. [26,106,107] Recently, ethyl acetate has been successfully used to recover LP produced by Pseudomonas [12,108] and Bacillus. [89] This organic solvent can be used to substantially reduce recovery expenses and minimize environmental hazards.…”
Section: Isolation and Purification Of Lpmentioning
confidence: 99%
“…Furthermore, biofilms are persistent and once formed are very difficult to remove. For these reasons, many groups are studying biofilms to determine how to block their formation (43)(44)(45)(46). Often, these studies use fluorescent proteins due partly to the stability and diversity of fluorescent reporters available.…”
Section: Biofilm Studiesmentioning
confidence: 99%